Student Entrepreneurship Cluster as The Implementation Response of University Entrepreneurship Program (A Case Study of Engineering Faculty Students of Unhasy Tebuireng) - Sulung Rahmawan Wira Ghani; Meriana Wahyu Nugroho (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2022)
Abstract This research was carried out to identify the characteristics of entrepreneurship carried out by students of the engineering faculty of Unhasy. The elements of cluster grouping are based on the entrepreneurial activities before becoming a student of the engineering faculty. This is to identify whether the activities have changed or not in terms of continued entrepreneurship after becoming a student at Unhasy. The processing of the data obtained shows that the program Entrepreneurship in the engineering faculty is identified based on: the alignment of the entrepreneurship program of Unhasy with implementation, the implementation of entrepreneurial practices, the entrepreneurship infrastructure that they have and want, the way to learn entrepreneurship, and the response to implementation of the Unhasy entrepreneurship program. From these variables, it shows in general that students of Unhasy's engineering faculty has been running entrepreneurship and survived until now at around 39%.